Additive manufacturing of polymeric composites from material processing to structural design. (15th August 2021) - Yuan, Shangqin; Li, Shaoying; Zhu, Jihong; Tang, Yulong
Abstract: Polymeric composites with multi-functionality offer significant advantages over metals, including lightweight, high strength and stiffness, corrosion and fatigue resistance, etc. Additively manufactured composites draw intensive attention over the past decade due to that they exhibit the large potential to extend their applications from rapid prototyping to functional end-use components. Moreover, advances in additive manufacturing (AM) open new perspectives for the next generation of design and manufacturing of composites, which possess spatially digitalized and materialized arrangement of material/structure in a voxel-by-voxel manner. This review examines the work performed in this fast-growing field and elaborates its future perspectives and potentials. Specifically, the polymer AM processes incorporating different types of reinforcements are discussed in terms of mechanism, feedstocks, their advantages, and constraints. Then, the AM-driven designs for polymeric composites on multiscale and for multi-functional applications are emphasized. Further, emerging research topics including digital composites, intelligence/data-driven design approaches, and four-dimensional printing are further addressed with the careful analysis of existing gaps and future research trends. Finally, this review is concluded with an outlook on future research opportunities on AM-fabricated composites from design to fabrication. This review aims to provide a comprehensive guide to the stakeholders who want to utilize or develop an AM process for polymeric composites.